A case study of the use of statistical processing of the armature rotation irregularities for the diagnostics of locomotive traction electric motors - Bodnar, Boris; Ochkаsov, Oleksandr; Hryshechkina, Tetiana; Petrenko, Viačeslav (Transport, 2025)
Locomotive Traction Electric Motors (TEMs) generate power to rotate the wheelsets of diesel or electric locomotives, electric or diesel multiple units. TEMs are the most critical parts of traction rolling stock on which exploitation costs, reliability and train traffic safety depend. The purpose of the article is to evaluate the possibility of diagnostics the technical condition of the TEM using the rotation irregularities of the armature shaft in the electric motor as a diagnostic parameter. The article analyses the main causes of TEM failures and methods for diagnosing electric motors in operation. The expediency of using the rotation irregularities of the armature shaft in the electric motor as a diagnostic parameter is substantiated. The structural flowchart of the device for measuring the rotation irregularities of the armature is presented. Diagnosing the mechanical part of an electric motor is chosen as an implementation example. The authors confirmed the connection between the technical condition of the electric motor and the statistical indicators calculated for the signal of the rotation irregularities of the armature shaft.